Baskexact: an R package for analytical calculation of basket trial operating characteristics - Baumann, Lukas (SoftwareX, 2024)
Basket trials are a new type of clinical trial in which a treatment is investigated in several subgroups. For the analysis of these trials, information is shared between the subgroups based on the observed data to increase the power. Many approaches for the analysis of basket trials have been suggested, but only a few have been implemented in open source software packages. The R package baskexact facilitates the evaluation of two basket trial designs which use empirical Bayes techniques for sharing information. With baskexact, operating characteristics for single-stage and two-stage designs can be calculated analytically and optimal tuning parameters can be selected.